2003
DOI: 10.1177/0021955x03039003001
|View full text |Cite
|
Sign up to set email alerts
|

Use of Real-time FTIR to Characterize Kinetics of Amine Catalysts and to Develop New Grades for Various Polyurethane Applications, Including Low Emission Catalysts

Abstract: The use of in situ Fourier Transform Infrared (FTIR) to follow PU reaction kinetics has been studied using a heated probe matching the PU material temperature. The results obtained show that, although not giving access to concentration of formed chemical bonds, the technique is a unique tool to assess subtle differences in catalysts behavior during actual PU formation, going beyond the currently used but restrictive characterization of catalysts in terms of gelling, blowing or trimerization grades. Examples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Previous studies utilizing fiber optic FTIR to monitor the reaction products of rigid polyurethane (PUR/PIR) foam for appliance manufacture has demonstrated that significant levels of isocyanurate were not detected at low (borderline) indexes (130-140) [10]. The influence of catalyst combinations on isocyanurate generation in PIR formulations has been monitored successfully by in situ FTIR [11]. It has been shown that along increasing index (200, 300, 500) the catalyst system of potassium octoate with JEFFCAT Õ1 Z-110 Catalyst demonstrates 1 JEFFCAT Õ and RUBINATE Õ are registered trademarks of Huntsman LLC in one or more, but not all, countries.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies utilizing fiber optic FTIR to monitor the reaction products of rigid polyurethane (PUR/PIR) foam for appliance manufacture has demonstrated that significant levels of isocyanurate were not detected at low (borderline) indexes (130-140) [10]. The influence of catalyst combinations on isocyanurate generation in PIR formulations has been monitored successfully by in situ FTIR [11]. It has been shown that along increasing index (200, 300, 500) the catalyst system of potassium octoate with JEFFCAT Õ1 Z-110 Catalyst demonstrates 1 JEFFCAT Õ and RUBINATE Õ are registered trademarks of Huntsman LLC in one or more, but not all, countries.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, much research aimed at studying their catalytic effect on polyurethane formation by using both theoretical and kinetic methods [11][12][13]. Thus, the catalytic process and selectivity in many cases are well understood [14].…”
Section: Of 11mentioning
confidence: 99%
“…Tertiary-amine-containing structures are usually used as catalysts in polyurethane reactions [ 11 ]. Therefore, much research aimed at studying their catalytic effect on polyurethane formation by using both theoretical and kinetic methods [ 11 , 12 , 13 ]. Thus, the catalytic process and selectivity in many cases are well understood [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…N,N-Dimethylcyclohexylamine (DMCHA) and tetramethylethylenediamine showed moderate activity between the gelling and the blowing reactions. For the development of new amine catalysts for FPUR foams, polyurethane reaction kinetics was followed using Fourier transform infrared spectroscopy (FTIR)-programmed cell to match the foam core temperature profile, which had a similar condition to the actual FPUR foam processing (4). Single catalysts and catalyst mixtures of commercially available amines were evaluated for FPUR preparation (5).…”
Section: Introductionmentioning
confidence: 99%